O professor do primeiro ano do Ensino Fundamental e suas representações sociais sobre o movimento corporal - Sá, Ivo Ribeiro de (2015)
The present paper aimed to present the analysis of social representations of Elementary School first grade teachers on body movement. When considering the scenario of political changes that expands the Elementary School to nine years and the identification of these social representations, it is possible to indicate whether the contents for the body and movement will be part or not of the school curriculum for six-year-old children, since the motor stimulation is crucial for child development and reflects the acquisition of motor skills in adulthood. In this sense, it was necessary to identify the influences of official documents in the constitution of social representations of the teacher on the body and movement. Therefore, it was chosen as the research field the city of Sao Bernardo do Campo, involving 8 school units and 31 Elementary School first grade teachers. Methodologically, it was decided to carry out this qualitative study in five phases. In the first one, official documents were analyzed from three subjects: child, movement and body. In the second one, a matrix was established to guide the construction and application of the interview script. In the third one, the material was prepared for data processing by the software ALCESTE. In the fourth one, categories of analysis generated from the relationship among the classes defined by ALCESTE were created. In the fifth one, the results found in the first and fourth phase were analyzed (MOSCOVICI, 1978, 2011) establishing relationships among them. The results revealed that the attitude of teachers regarding the body movement is to promote recreational moments and let the child free to play, that is, there is the recognition of recreational purposes, but without setting specific goals. They justify this position due to lack of preparation to work with the content related to the child's body and movement and assign this function to the specialist teacher and the lack of school infrastructure. Thus, they emphasize literacy in the first grade of Elementary School and minimize the time to develop the knowledge about body and movement. With the expansion of Elementary School to nine years, its pedagogical practices have suffered few changes. The only change mentioned was the increased time for children to play. However, despite the recognition that playfulness in the teaching process is a right of the child, they have proven resistant to apply such educational practices due to requirements of the school for literacy. They believe that the body movement can serve as a tool for learning reading, writing, mathematics etc., exerting an auxiliary role in the educational process. This creates a polarization between the moments of play and the ones intended for writing and reading instruction. Thus, from the observation of social representations, it is possible to say that a fragmentary view of human formation still remains among the teachers, leading to the conclusion that the idea of integral formation in the official documents is far from being achieved